2014
DOI: 10.1177/2050640614553285
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of fecal immunochemical test in average‐ and familial‐risk colorectal cancer screening

Abstract: Background: There is little information about the fecal immunochemical test (FIT) in familial-risk colorectal cancer (CRC) screening. Objectives: The objective of this article is to investigate whether FIT diagnostic accuracy for advanced neoplasia (AN) differs between average and familial-risk (first-degree relative) patients. Methods: A total of 1317 consecutive participants (595 familial) who collected one stool sample before performing a colonoscopy as a CRC screening test were included. FIT diagnostic acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
17
2
Order By: Relevance
“…Additionally this information could explain one of the most striking ndings of our study. Although males have an increased risk of advanced neoplasia detection in CRC screening [28] and account for 75% of the high risk lesions detected, [29] in our study, females have an increased risk of surgery. The reason is unclear and we suggest it may be related to differences in the natural history of CRC.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally this information could explain one of the most striking ndings of our study. Although males have an increased risk of advanced neoplasia detection in CRC screening [28] and account for 75% of the high risk lesions detected, [29] in our study, females have an increased risk of surgery. The reason is unclear and we suggest it may be related to differences in the natural history of CRC.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, a retrospective study comparing the performance of FIT (OC-Sensor, cut-off 20 mcg Hb/g feces) in average risk patients enrolled in the colonoscopy arm of the COLONPREV trial ( 10 ) and individuals with a FDR with CRC showed similar sensitivities and specificities for the detection of advanced neoplasia between the two patient populations ( 11 ). In addition, there was no difference in FIT performance when comparing the number of FDRs with CRC or their age of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the same screening strategy as that for average-risk individuals could be recommended to men and women having only one FDR with colorectal cancer, but starting at the age of 40 or 45 y, in line with the results of previous studies [ 5 , 30 ], thus avoiding overuse of screening colonoscopy. In support of this recommendation, there are two recent prospective studies demonstrating that fecal immunochemical testing is as effective as colonoscopy to detect advanced neoplasia in colorectal cancer associated with familial risk [ 19 , 41 ]. In contrast, the higher prevalence and earlier presentation of advanced neoplasia in men having two FDR with colorectal cancer suggest that men have higher genetic penetrance, thus supporting screening colonoscopy from the age of 40, whereas it could be delayed until the age of 50 or older in women with two FDR.…”
Section: Discussionmentioning
confidence: 99%